2022
DOI: 10.1186/s12958-022-00932-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of SK3 in progesterone-induced inhibition of human fallopian tubal contraction

Abstract: Background Normal motor activity of the fallopian tube is critical for human reproduction, and abnormal tubal activity may lead to ectopic pregnancy (EP) or infertility. Progesterone has an inhibitory effect on tubal contraction; however, the underlying mechanisms remain unclear. Small-conductance calcium-activated K+ channel 3 (SK3) is abundantly expressed in platelet-derived growth factor receptor α positive (PDGFRα+) cells and was reported to be important for the relaxation of smooth muscle.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The potassium (K + ) channel has important effects on reproductive health outcomes, and can be involved in outcomes such as malformation of the fallopian tube [ 36 ], and male infertility [ 37 ]. A population study reported that women with PCOS had a lower potassium intake than women in a control group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potassium (K + ) channel has important effects on reproductive health outcomes, and can be involved in outcomes such as malformation of the fallopian tube [ 36 ], and male infertility [ 37 ]. A population study reported that women with PCOS had a lower potassium intake than women in a control group [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that PRs are expressed on the ICC and PDGFRα + cells of the fallopian tube smooth muscle and are involved in the regulation of tubal peristalsis acting as sensors by integrating the major pacemaker function with signaling mechanisms [ [23] , [24] , [25] ]. Based on these findings, we suspected that progesterone may be involved in the regulation of gastrointestinal motility disorders.…”
Section: Introductionmentioning
confidence: 99%